An outline of the law of contract - Treitel,G.H (London : Butterworths, 1984)
The book sets out the general principles of law of contract. It tries to expose the fundamental difficulties of the subject and some of the defects of the law.
Includes index
obn 25/01/2019
Loans
Keywords: Contracts; Great Britain